2002
DOI: 10.1086/340436
|View full text |Cite
|
Sign up to set email alerts
|

The Soft Gamma‐Ray Spectral Variability of Cygnus X‐1

Abstract: We have used observations of Cyg X-1 from the Compton Gamma Ray Observatory and BeppoSAX to study the variation in the MeV -ray emission between the hard and soft spectral states, using spectra that cover the energy range from 20 keV up to 10 MeV. These data provide evidence for significant spectral variability at energies above 1 MeV. In particular, whereas the hard X-ray flux decreases during the soft state, the flux at energies above 1 MeV increases, resulting in a significantly harder -ray spectrum at ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
286
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(316 citation statements)
references
References 67 publications
27
286
2
Order By: Relevance
“…Following the model by Zdziarski & Gierliński (2004), another possible source of gamma rays, especially in the low/hard spectral state, is the high-energy tail of the electron distribution in the corona. Instead in the high/soft state, the energy spectrum does not show an energy cutoff, as confirmed by the COMPTEL detection up to ∼10 MeV (McConnell et al 2002) and a gamma ray emission above this energy is expected.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Following the model by Zdziarski & Gierliński (2004), another possible source of gamma rays, especially in the low/hard spectral state, is the high-energy tail of the electron distribution in the corona. Instead in the high/soft state, the energy spectrum does not show an energy cutoff, as confirmed by the COMPTEL detection up to ∼10 MeV (McConnell et al 2002) and a gamma ray emission above this energy is expected.…”
Section: Introductionmentioning
confidence: 61%
“…Interestingly, Cyg X-1 was also detected by COMPTEL in high/soft state, up to about 10 MeV energy (McConnell et al 2002). At that time the EGRET instrument was switched off and no GeV observation is available.…”
Section: The Search For Gamma Ray Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b, panels 10 and 11. The high-and low-state spectra intersect at $400 keV, compared to those observed for GRO J0422+32 at $600 keV ( Ling & Wheaton 2003a) and Cygnus X-1 at $1 MeV McConnell et al 2002). contemporaneously with OSSE periods A and B showed a slightly better fit with the exponential truncated power law than the power law ( Table 6).…”
Section: Spectramentioning
confidence: 80%
“…GRO J1719À24, a low-mass X-ray binary system with a 14.7 hr periodicity, consisting of a $4.9 M compact object and a $1.6 M companion star ( Della Valle et al 1994;Masetti et al 1996), is one of three Galactic black hole systems, along with GRO J0422+32 ( Ling & Wheaton 2003a) and Cygnus X-1 ( Phlips et al 1996;Ling et al 1997;McConnell et al 2000McConnell et al , 2002, that displayed similar gamma-ray spectral characteristics when undergoing transitions between the high and low gammaray intensity states 1. When these sources were in the high gamma-ray intensity state ( 2 for Cygnus X-1; Ling et al 1997), their spectra showed two components: a Comptonized component from $30 to $200 keV followed by a soft power-law tail of photon index >3 above $200 keV that extended to $500 keV for GRO J1719À24, $1 MeV for Cygnus X-1 ( Ling et al 1997;McConnell et al 2000), and $600 keV for GRO J0422+32 ( Ling & Wheaton 2003a).…”
Section: Discussionmentioning
confidence: 99%